CodeToProtect / Mohd Syazran Mazlan - Mazlan, Mohd Syazran (Universiti Teknologi MARA, Kedah, 2019)
Educational video game is slowly becoming the main trend here in education industry as more and more media based and game based educations are being published every year to cater towards the rising demands of this particular type of learning. Educational video game is said to be the future of learning as it is said to fit the current generation style of learning better than the previous generation. This also means educational video game had also spread to the use of programming subject as well as conventional programming education is found to be not as effective as it used to. Although many programming educational video game are published today, there is a gap that is yet to be filled which is video game that teaches C++ programming language. The problem is the lack of C++ programming language to teach higher education learners as C++ is proven to be the most used programming language here in Malaysia’s education system. CodeToProtect© is a video game that will fill in the gap by teaching the language of C++ programming to the higher education learners in Malaysia. The game is intended to help students in understanding the concept of programming. By developing the game, it will be able to benefit more students as C++ is widely used in Malaysia’s education hence improving the overall quality of programming education here in Malaysia.